Characterization and Differential Cytotoxicity of Gramicidin Nanoparticles Combined with Cationic Polymer or Lipid Bilayer - Yunys Pérez-Betancourt; Rachel Zaia; Marina Franchi Evangelista; Rodrigo Tadeu Ribeiro; Bruno Murillo Roncoleta; Beatriz Ideriha Mathiazzi; Ana Maria Carmona-Ribeiro (MDPI AG, 2022)
Gramicidin (Gr) nanoparticles (NPs) and poly (diallyl dimethyl ammonium) chloride (PDDA) water dispersions were characterized and evaluated against Gram-positive and Gram-negative bacteria and fungus. Dynamic light scattering for sizing, zeta potential analysis, polydispersity, and colloidal stability over time characterized Gr NPs/PDDA dispersions, and plating and colony-forming units counting determined their microbicidal activity. Cell viabilities of Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans in the presence of the combinations were reduced by 6, 7, and 7 logs, respectively, at 10 μM Gr/10 μg·mL−1 PDDA, 0.5 μM Gr/0. 5μg·mL−1 PDDA, and 0.5 μM Gr/0.5 μg·mL−1 PDDA, respectively. In comparison to individual Gr doses, the combinations reduced doses by half (S. aureus) and a quarter (C. albicans); in comparison to individual PDDA doses, the combinations reduced doses by 6 times (P. aeruginosa) and 10 times (C. albicans). Gr in supported or free cationic lipid bilayers reduced Gr activity against S. aureus due to reduced Gr access to the pathogen. Facile Gr NPs/PDDA disassembly favored access of each agent to the pathogen: PDDA suctioned the pathogen cell wall facilitating Gr insertion in the pathogen cell membrane. Gr NPs/PDDA differential cytotoxicity suggested the possibility of novel systemic uses for the combination.